2023
DOI: 10.3390/biomedicines11051265
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Markers for Normal Pressure Hydrocephalus: An Overview

Abstract: Idiopathic bormal pressure hydrocephalus (iNPH) is a neurological syndrome that clinically presents with Hakim’s triad, namely cognitive impairment, gait disturbances, and urinary incontinence. The fact that iNPH is potentially reversible makes its accurate and early diagnosis of paramount importance. Its main imaging characteristic is the dilation of the brain’s ventricular system and the imaging parameters are also included in its diagnostic criteria along with clinical data. There is a variety of different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 111 publications
0
4
0
1
Order By: Relevance
“…Computed tomography (CT) scans are the major routine method for evaluating brain morphology in both developed and developing countries but typically rely on subjective visual inspection and ratings 43,44 . Adopting reliable automated and quantitative methods, such as machine learning for ventricular segmentation, could substantially improve the diagnostic performance of CT-derived data through enhanced accuracy and consistency, reducing inter-rater variability, and providing substantial benefits in both research and clinical contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Computed tomography (CT) scans are the major routine method for evaluating brain morphology in both developed and developing countries but typically rely on subjective visual inspection and ratings 43,44 . Adopting reliable automated and quantitative methods, such as machine learning for ventricular segmentation, could substantially improve the diagnostic performance of CT-derived data through enhanced accuracy and consistency, reducing inter-rater variability, and providing substantial benefits in both research and clinical contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Вентрикуломегалия, выявляемая методами нейро визуализации, может быть следствием атрофии или гидроцефалии. Гидроцефалия может блокировать восстановление сознания, а ликворошунтирующие операции могут способствовать процессам его восстановления [122][123][124][125].…”
Section: коррекция посттравматической гидроцефалииunclassified
“…These studies underscore that two-dimensional ventricular morphometry for quantifying ventricular enlargement is nonspecific and insufficient as independent diagnostic or prognostic indicators for iNPH. Moreover, it fails to explain the typical triad symptoms of iNPH patients ( Espay et al, 2017 ; Mantovani et al, 2020 ; Pyrgelis et al, 2023 ).…”
Section: Introductionmentioning
confidence: 98%
“…It has been widely applied in studying the structural characteristics of the brain in various neurodegenerative diseases (Hutton et al, 2008;Kang et al, 2018). Previous researches in animal models and children with hydrocephalus has reported an association between increasing ventriculomegaly and more marked thinning of the cerebral cortex (Olopade et al, 2012;Pyrgelis et al, 2023). A study revealed that total cortical thickness was thinner in the iNPH group compared with the control group (Moore et al, 2012).…”
Section: Open Access 1 Introductionmentioning
confidence: 99%